The Community Charter on Data and AI: Creating an actionable social license for sharing health and civic data in the Liverpool City Region - Rempel, Emily (International Journal of Population Data Science, 2026)
In 2025, the Liverpool City Region (LCR) Civic Data Cooperative set out to establish a set of principles on what trustworthy and beneficial data and AI use means for LCR residents. Sometimes called a social license or a Charter, sets of principles help organisations align their practices to what communities and publics want to see happen. We used a Residents’ Assembly methodology to create our Charter. Assemblies, or juries, are a deliberative mini-public methodology that puts one or two core questions to a representative group of community members to provide policy recommendations. We recruited 59 residents, representative of geographical and demographic differences, to hear evidence from expert speakers and share back their perspectives. We present findings from the Assembly as well as reflections on running large-scale deliberative exercises on data. We collected data through an anonymous Ranked Choice Vote on day 4 of the Assembly, voice recordings from days 3 and 4, and ethnographic notes from facilitators. The principles were produced through the ranked choice vote. We used thematic analysis to explore wider views of residents from transcripts. Residents’ views were complex but highlighted three core themes: fear of harm underpinned by hope for change, concerns on power imbalances preventing community benefit, and the unknowable future of AI harming human ingenuity. The final eleven item Community Charter on Data and AI includes concepts around privacy, governance, and community benefit and has been ratified by the NHS Cheshire & Merseyside ICB, the University of Liverpool, and the LCR Combined Authority.